Remote Simulation: A Binational Innovative Experience in Teaching Forensic Medicine for Medical Students during the COVID-19 Pandemic - Segura Aparicio, Jean Carlo (2024)
The Covid-19 pandemic necessitated the closure of clinical spaces for medical student training worldwide, prompting medical schools to seek alternative methods to sustain academic activities. At the University of Costa Rica, technological tools were integrated into all courses, including Forensic Medicine. Leveraging an existing agreement between the Forensic Medicine departments of the University of Costa Rica and the University of Panama, the didactic strategy employed in Costa Rica, which utilized technological platforms and standardized patients, was shared with Panamanian educators and students through an extension course. This study aims to evaluate the impact of these technologies on this educational experience. A four-week, fully virtual course was conducted using Zoom and Moodle platforms, with bi-weekly, two-hour synchronous sessions. The course enrolled 64 students from the University of Panama, with assessment based on class participation, short tests, and a final exam. Results indicated a strong correlation between attendance at simulation sessions and final grades, with higher participation leading to better performance, independent of gender. As the course progressed, students demonstrated improved understanding of forensic medicine concepts, reflected in their final grades. The study concludes that this didactic strategy was effective during the Covid-19 crisis, providing essential support from the University of Costa Rica to Panamanian counterparts. Continued replication of such courses and the inclusion of real-time simulation practices aligned with specific learning objectives are recommended.